A Case Report on Nivolumab Induced Hypophysitis - A, Ancy; K, Kavyasree; Finny, Philip; George, Shone Padinjarethil (Indian Journal of Pharmacy Practice)
Nivolumab, an immune checkpoint inhibitor, has revolutionized the treatment of various malignancies, including esophageal adenocarcinoma. However, its use is associated with immune-related Adverse Events (irAEs), including hypophysitis, a rare but potentially serious inflammation of the pituitary gland. This case report describes a patient with adenocarcinoma of the lower esophagus who developed hypophysitis after five cycles of nivolumab, presenting with hyponatremia and low cortisol levels. This case highlights the importance of recognizing and managing this endocrine irAE in patients undergoing immunotherapy.
Keywords: Nivolumab; Hypophysitis; Immune Checkpoint Inhibitor; Adverse Events; Esophageal Adenocarcinoma; Immunotherapy